A humanidade coisificada pelo capital: apreensão da categoria reificação e sua recuperação ontológica pelo percurso formativo marxiano-lukacsiano - Carvalho, Ana Paula Monteiro de (2021)
The complexity of social life in its contradictory reproduction, led by the objective fragmentation of the social being perpetrated by the commodity fetishism, generated multiple apprehensions of the investigated category, heterogeneity that we call, inspired by Lukács, different degrees of determination’s apprehension from the reified society which it must be unveiled to the closest degree of the objective reality. In our Marxian assumption that is drawn from historicity: the trajectory of reality’s apprehension always has an ontological character, whether the social being is aware of it or not, since it constitutes the relationship between being and thought; that is, the ability to reproduce the ideal movement of the objective determinations that allow it to produce its existence. In light of the above, the general objective of this research is to analyze the degrees of apprehension of reification by the consciousness of the social being in its historical-formative course. This path, which is non-linear, we call the historicalformative path of the social being’s consciousness. To lead this investigation in a more refined way, we established the following specific objectives: 1) to restore the path that Marx followed for discovered the fundamentals about the commodity fetishism, which is the genesis of reification and culminated in the great work “Capital. Critique of Political Economy”. 2) to analyze the determinations and mediations of the reification’s category found by Lukács in his formative path, which it was emphasized in his two publications: “History and Class Consciousness” and “The Ontology of Social Being”. 3) to situate the current degree of apprehension from reification’s category in Brazilian academic thinking, that identify the approximations and distances from the Marxian-Lukacsian legacy. 4) to extract from the formative paths of Marx and Lukács the elements of the ontological approach about the process of education’s reification while a praxis unfolded from the relations of production, which articulate the concrete Totality of the social complexes and, above all, as a spiritual production from the human race essentiality to the social reproduction, to human formation, assuming that reification is part of the process of social reproduction and is intrinsically related with it. The theoretical-bibliographic-documental research, with the current appropriation of Brazilian academic thinking, mapped the approximations and distances from the discoveries of these two authors, Marx and Lukács. A search in thesis and dissertation database from CAPES (Coordination for the Improvement of Higher Education Personnel) for information about the category of reification provided an organization that separated the data in common groups of theoretical approximation and / or distance from the Marxian ontology. From the investigative effort we draw some conclusions. Thesis 1: Recovery of the Commodity Fetishism as the ontological basis of the Reification process, considering the categorical emptiness generated throughout the process advanced capitalism’s development and the new mystifications created by historical socialism; thesis 2: Ontological character of the theoretical trajectories from Marx and Lukács, since Youth to Maturity. The continuities and discontinuities were historically determined by the path of human race, which confronted, assimilated and elevated themselves, in a process of successive social reality’s approximations with the objective of offer to the social being the method necessary for the construction of the praxis emancipating from capital; thesis 3: The increasing autonomisation of the education complex as an important element of the Reification process it is a result of the increase of dead labor in the organic composition of capital, what potentiate exploitation by capital. Finally, we find that Reification is part of the process of social reproduction and is intrinsically related.